An Assessment of the Macroeconomic Implications of COVID-19 in Nepal: Evidence from SIR –Macro Model Analysis - Katuwal, Khagendra; Prakash, Manab; Adhikari, Naveen; Raut, Nirmal Kumar; Adhikari, Shiva Raj (Economic Journal of Nepal, 2021)
This paper assesses the macroeconomic implications of COVID-19 in the context of Nepal. The study uses a susceptible, infected, and recovered macro model (SIR-Macro model) where epidemiological variables are interacted with macroeconomic variables namely consumption and working hours to simulate the implication. The model estimates show that the containment measures of the government reduced the spread of the disease by 17 percent. However, the COVID-19 pandemic had a significant negative impact on macroeconomic outputs. On average, both consumption and working hours declined by 20 percent which otherwise would be more serious if no containment measures were adopted. In addition, the study also finds that the impact has been heterogeneous across susceptible, infected, and recovered population. Interestingly, the study also indicates that the individual utility lowered while societal utility improved with containment policies.